From Hesitation to Confidence: The Role of AI Speaking Partners in Independent Language Learning - Sulistiana, Eva; Arda Adianto; Wardatun Nadzifah (International Journal of English and Applied Linguistics (IJEAL), 2025)
This study was motivated by students' low self-confidence and English speaking skills, which were influenced by weak learning motivation and limited learning media that lacked variety. Artificial intelligence (AI) offers an innovative solution through interactive applications that can function as personal practice companions. Preliminary study results from interviews with students at MA Model Zainul Hasan show that 75% of students have below-average speaking skills, which is caused by a lack of confidence and limited time for practice. This study aims to determine the effect of using AI as a practice companion on improving students' confidence and English speaking skills. The method used is pre-experimental with a one group pre-test and post-test design, involving 84 students as samples. The research instruments are confidence questionnaires and speaking skill assessments. The results of the analysis using the paired sample t-test showed a significant increase after the intervention: the average confidence increased from 58.95 to 67.08 (p = 0.000), and speaking skills increased from 55.67 to 66.17 (p = 0.000). These findings prove that the use of AI can significantly improve students' self-confidence and speaking skills. This study contributes to the use of technology in English language learning, particularly in developing students' speaking skills and self-confidence. Keywords: AI, self-confidence, speaking skills, high school students, English language learning